Penggunaan Multimedia Cai Pada Pembelajaran Mekanik Otomotif Kompetensi Pemeliharaan Rem Hidrolik Di SMK - Rohendi, Dedi; Hendarwin, Hendry (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2010)
The implementation of vocational school curriculum was noticed a difference learning from complexand abstract concepts become more simple, concrete, and easy to understand. One solution to handle thatproblem is a multimedia learning with CAI. This study aims to obtain a real condition of increasing students'mastery learning of the material also compared the differences between student learning using multimedia CAIwith conventional learning. Research method used was quasi-experimental methods are conducted to 30 studentas an experiment samples and the control group with the number of samples of 30 people. The results showedthat students who use multimedia CAI can learn to fully implement the concept and the concept of independentlearning and competency based. Learning by using multimedia CAI can improve student’s mastery learning andhelp to deliver student to achieve a complete mastery of competency and inprove the students mastery of thematerial with a significant difference compared with students who are not using the multimedia CAI.